Efficacy of florfenicol for the treatment of Staphylococcus intermedius pyoderma in dogs - Tameirão, Emanuely Ramos (2021)
The aim of this study was to evaluate the effect of florfenicol treatment at doses of 10 and 20 mg/kg administered IM, in the treatment of canine pyoderma due to Staphylococcus intermedius, using pharmacokinetic/pharmacodynamic modelling (PK/PD). A Monte Carlo simulation of the pharmacokinetic and pharmacodynamic parameters was performed, followed by a PK/PD modelling to determine the efficacy rates in the treatment of bacterial infection, according to the minimum inhibitory concentration (MIC) of S. intermedius, using the range between 0.25 and 2 µg/ml. The probabilities of obtaining the bacteriological eradication index with the 10 mg/kg dose were 97, 77, 7 and 1%, and with the 20 mg/kg dose it was 95, 87, 61 and 7%, according to bacterial MICs of 0.25, 0.5, 1 and 2 µg/ml, respectively. The probability of obtaining a bacteriological cure after treatment with the 10 mg/kg dose decreased significantly for infections caused by microorganisms with MICs higher than 0.5 µg/ml (p<0.01), while for the 20 mg/kg dose kg was with MIC greater than 1 µg/ml (p<0.01). The results show the need to incorporate bacteriological isolation, the determination of MIC and the optimization of therapeutic doses based on bacterial susceptibility in the therapeutic protocol in order to avoid therapeutic failures and, consequently, the increase in the development of microbial resistance.